Peranan Remaja Masjid Darussalam dalam Meningkatkan Kualitas Shalat Berjamaah di Masjid Desa Rambah Muda - Eka Novia Rahmaningrum; Sudar Manto; Viky Ardi; Musa Thahir; Rian Vebrianto (Anotero Lembaga Scientific Pekanbaru, 2021)
The mosque can be said to be the identity of Muslims, because the mosque is used as a place of worship for Muslims. With the passage of time the mosque has developed both in terms of construction and function of the mosque. If you see today's mosques are built very luxuriously with a phenomenon like this, it indicates that Muslims are progressing, but on the other hand the mosque is experiencing a shift in function that is far from a value of prosperity. The prosperity of a mosque depends on the youth who bring the mosque to life. For this reason, the researcher as a servant with the real work course wants to give a role for mosque youth to serve as a stimulus for the congregation to be active in performing congregational prayers and participating in activities in the mosque. The instrument used is an evaluation questionnaire obtained from six Darussalam mosque youth work programs in improving the quality of congregational prayers at the mosque. The result of this service is that the Monthly Recitation, holds religious lectures, commemorates Islamic holidays and holds Islamic spirituality every month. there is a significant influence between the role of mosque youth in improving the quality of congregational prayers at the Darussalam Mosque, Rambah Muda Village.